A comparative study of construction contracts under the Iraqi Civil Law and Shari'ah - Yaseen, Hajar Gamal (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
Construction contracts are considered as one of the high risk contracts because of their features such as long and fixed period, complicated processes, unexpected environment, financial intensity and large number of employees. This research analyzes the existing construction contract under the Iraqi Civil Code No. 40 of 1951 and the principles of construction contract under the Shariah. The main objective of the research is to examine whether the Iraqi Civil Code is in compliance with the Shariah principles. The Iraqi Civil Code has the influence of the Egyptian law and French Civil Code. Although it incorporates the Islamic principles, its overall structure and substance is principally based on civil law. It shares common substance and legal theory with other civil legal systems such as in Egypt and France. This research applies the legal research methodology which focuses on doctrinal study. The study relies on inductive method of collecting the Islamic jurists views on construction contracts (Istisnā), as well as uses comparative method to compare Shariah with the Iraqi Civil Code. It is observed that although most of the terms in Iraqi Civil Code contained in Articles 864-890 are consistent with the Shariʻah provisions, there are still few differences between the two laws due to the impact of the French and Egyptian Civil Code on the Iraqi Civil Code. This study recommends that some of the provisions in the construction contract under the Iraqi Civil Code should be amended to comply with the Shariah requirements and to keep pace with development requirements of the country.